2008
DOI: 10.1007/s11519-008-0034-4
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric laterality in music and math

Abstract: Hemispheric laterality may be a useful concept in teaching, learning, training, and in understanding more about human development. To address this issue, a measure of hemispheric laterality was compared to musical and mathematical ability. The Human Information Processing Survey (HIPS) instrument, designed to measure hemispheric laterality, was administered to 101 participants who were then asked to provide a measure of their conceptual aptitude for mathematics and music. Scores were then compared through cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Many other studies have found right hemisphere dominance for a range of musical tasks (e.g. melody: Kimura, 1964;pitch and loudness: Nachson, 1978; self-perceived musical ability: Szirony, Burgin & Pearson, 2008).…”
Section: Laterality Of Music Perceptionmentioning
confidence: 94%
“…Many other studies have found right hemisphere dominance for a range of musical tasks (e.g. melody: Kimura, 1964;pitch and loudness: Nachson, 1978; self-perceived musical ability: Szirony, Burgin & Pearson, 2008).…”
Section: Laterality Of Music Perceptionmentioning
confidence: 94%
“…Flexibility or brain efficiency is related to brain hemisphericity [hemispheric lateralization], often called brain coherence (Garrison, 2003; Griffiths, Ryan, & Foster, 2011), or the ability to freely switch between brain hemispheres, where the left hemisphere generally responds to language and the right hemisphere to spatiality (Anderson, 2010; Gier, Kreiner, Solso, & Cox, 2009; Stankov et al, 2006; Taggart & Torrance, 1984). Thinking abstractly and flexibly are attributes of mindfulness, and directly impact decision making, problem solving, and creativity (Duckworth, Peterson, Matthews, & Kelly, 2007; Friedlander et al, 2011; Szirony, Burgin, & Pearson, 2008; Treffinger et al, 2008), and represent neo-cortical and prefrontal cortex operations (Blair, 2006; Meltzer, 2007; Yu, Ryan, Schaie, Willis, & Kolanowski, 2009), the areas related to higher-order thinking and creative behavior (Matindale, 1999). Mindfulness is a purposeful metacognitive strategy enabling an individual to stay focused and motivated, thereby preventing extraneous factors from interfering with a completion mindset.…”
Section: Brain Optimization As a New Learning Theorymentioning
confidence: 99%